Changes in Catastrophic Health Expenditures Depending on Health Policies in Turkey - Kockaya, Guvenc; Oguzhan, Gülpembe; Çalşkan, Zafer (Frontiers in Public Health, 2021)
Without any financial protection out of pocket health expenses are essential both because their increase causes difficulties in accessing higher quality health services for households and more importantly because it complicates access to most basic health services. As a result of the Health Transformation Program in practice in the Turkish healthcare system since 2003, significant changes have been done in all layers of the health system. Turkish Statistics Institute (TurkStat) publishes the ratio of households that bear catastrophic health expenditures since 2002. According to TurkStat data, the ratio of households with catastrophic expenditure has fallen from 0.81% in 2002 to 0.17% in 2011 with the health transformation project. However, it has started to rise since 2012 and has reached 0.31% in 2014. This study aims to evaluate the expenditure items that may have caused the rise of the ratio of households with catastrophic health expenditures since 2012, which had previously dropped with the Health Transformation Program that has caused fundamental changes in health policies. Methodology and definitions presented in the article named “Distribution of health payments and catastrophic expenditures: Methodology” by Ke Xu published by the World Health Organization in 2005 have been used. Percentages of health expenditure items among the total expenditure of households with positive health expenditure and households with catastrophic health expenditure between 2007 and 2014 have been evaluated using descriptive analysis. Findings have been interpreted in light of the health policies in practice between 2007 and 2014. An overview of the impact of the health policies reveals that medicine expenditures have decreased both for household and public health expenditures. Despite the impact of policies on the pharmaceutical industry was criticized by the industry, the positive impact can be seen by the decrease in the spending on medicine for households spending on health. Hospital service with positive health expenditure is seen to decrease health expenditure. The reasons for the increase in households with catastrophic health expenditure need further research. As a result, the study strives to discuss the possible policy reasons for the observed effects.